Keragaan Produk Hair Tonic Polihebal Berbasis Limbah Dedak Padi Berteknologi Nano dan Karakteristik Konsumennya - Talitha Zahira Hendriadi; Ernah Ernah; Vira Kusuma Dewi (Universitas Galuh, 2026)
The personal care industry holds significant potential due to high societal usage rates. Freshair is a polyherbal hair care product developed from rice bran waste and enhanced through the application of nanotechnology to support optimal absorption. Launched in 2024, it garnered positive responses with sales revenue which is quite high. This research aims to describe the general overview of the Freshair producer and product, as well as identify consumer characteristics. The study employs descriptive qualitative and quantitative methods. Data were collected through surveys using probability sampling, with a population of 268 individuals and a sample of 75 respondents. Primary data came from consumer questionnaires and internal interviews with the management team. Secondary data were sourced from literature. Analysis included validity and reliability tests of instruments, followed by descriptive analysis to depict business performance and consumer characteristics based on variables such as age, gender, education, income, and occupation. Results indicate Freshair's business performance encompasses an innovative product priced at Rp39,000 per 100 ml, produced in West Java, distributed online and offline to four provinces, operated by five individuals, and promoted through discounts, mass media publications, social media, and endorsements. In conclusion, Freshair consumer characteristics are predominantly late adolescents, females, with S1 education, and students/scholars with no independent income.